Hospitalizations during the last months of life of nursing home residents: a retrospective cohort study from Germany - Specht-Leible Norbert; Ramroth Heribert; König Hans-Helmut; Brenner Hermann (BMC, 2006)
Abstract Background To describe hospitalisations of nursing home (NH) residents in Germany during their last months of life. Methods Retrospective cohort study on 792 NH residents in the Rhine-Neckar region in South-West Germany, newly institutionalized in the year 2000, who died until the study end (December 2001). Baseline variables were derived from a standardized medical examination routinely conducted by the medical service of the health care insurance plans in Germany. Information on hospitalisations and deaths was extracted form records of the pertinent health insurance plans. Results NH residents who died after NH stay of more than 1 year spent 5.8% of their last year of life in hospitals. Relative time spent in hospitals increased from 5.2% twelve months before death (N = 139 persons) to 24.1% in their last week of life (N = 769 persons). No major differences could be observed concerning age, gender or duration of stay in NH. Overall, 229 persons (28.9%) died in hospital. Among these, the last hospital stay lasted less than 3 days for 76 persons (31.9%). Another 25 persons (3.2%) died within three days after hospital discharge. Conclusion Our study indicates that proximity of death is the most important driver of health care utilization among NH residents. The relation of age or gender to health care expenditures seem to be weak once time to death is controlled for. Duration of NH stay does not markedly change rates of hospitalisation during the last months of life.